PENGARUH LATIHAN PERMAINAN TARGET TERHADAP KETEPATAN SHOOTING DALAM PERMAINAN EKSTRAKURIKULER FUTSAL DI SMP MANDIRI PALEMBANG - Fernando Hasibuan; Perabu Nita; I Made Andika Bayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Target game practice is related to the object or goal to be achieved. In the game of futsal, shooting accuracy is a key factor because the chances of scoring goals in futsal often occur in tight spaces and limited time. Based on this, the problem in this study is whether there is an effect of target game training on shooting accuracy in futsal extracurricular games. The purpose of this study is to determine the effect of target game practice on shooting accuracy in futsal extracurricular games at Mandiri Palembang Junior High School. The research method used is a quantitative method of experiment type. Based on the calculation of the hypothesis test using the SPSS 26 application, it was obtained from the t-calculation value of 7.524 with a t-table value of 1.729 with df = n – 1 where n = 20 so df = 20 – 1 = 19. Thus, the t-calculation value is 7.524 ≥ t-table is 1.729, H0 is rejected and Ha is accepted or the results of the study show that there is an influence of target game practice on shooting accuracy in extracurricular futsal students of Mandiri Palembang Junior High School.